Vitamin E, γ-tocotrienol, Protects Against Buthionine Sulfoximine-Induced Cell Death by Scavenging Free Radicals in SH-SY5Y Neuroblastoma Cells. (2nd April 2016) - Tan, Jen-Kit; Then, Sue-Mian; Mazlan, Musalmah; Jamal, Rahman; Ngah, Wan Zurinah Wan
ABSTRACT: The induction of reactive oxygen species (ROS) to selectively kill cancer cells is an important feature of radiotherapy and various chemotherapies. Depletion of glutathione can induce apoptosis in cancer cells or sensitize them to anticancer treatments intended to modulate ROS levels. In contrast, antioxidants protect cancer cells from oxidative stress-induced cell death by scavenging ROS. The role of exogenous antioxidants in cancer cells under oxidative insults remains controversial and unclear. This study aimed to identify protective pathways modulated by γ-tocotrienol (γT3), an isomer of vitamin E, in human neuroblastoma SH-SY5Y cells under oxidative stress. Using buthionine sulfoximine (BSO) as an inhibitor of glutathione synthesis, we found that BSO treatment reduced the viability of SH-SY5Y cells. BSO induced cell death by increasing apoptosis, decreased the level of reduced glutathione (GSH), and increased ROS levels in SH-SY5Y cells. Addition of γT3 increased the viability of BSO-treated cells, suppressed apoptosis, and decreased the ROS level induced by BSO, while the GSH level was unaffected. These results suggest that decreasing GSH levels by BSO increased ROS levels, leading to apoptosis in SH-SY5Y cells. γT3 attenuated the BSO-induced cell death by scavenging free radicals.